The incentives to form research joint ventures: theory and evidence - Lars-Hendrik Röller; Mihkel M. Tombak; Ralph Siebert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
The literature on research joint ventures (RJVs) has emphasized internalizing spillovers and cost-sharing as motives for RJV formation. In this paper we develop two additional explanations: product market complementarities and firm heterogeneity. We analyze a model of RJVs with asymmetric firms and differentiated products. We then test these various explanations for RJV formation by estimating an endogenous switching model using data now available through the U. S. National Cooperative Research Act. – – Die Literatur über Forschungs-Joint-Ventures (FJV) hat bisher die Internalisierung von Spillovers und die Kostenaufteilung als primäre Motive, ein FJV zu gründen, hervorgebracht. In diesem Beitrag werden zwei weitere Gründe angeführt: Produktmarktkomplementaritäten und Unternehmensheterogenitäten. Wir analysieren ein Modell über FJV mit asymmetrischen Unternehmen und differenzierten Produkten. Anschließend testen wir die verschiedenen Erklärungen, ein FJV zu gründen. Hierbei wird ein endogenes ,,switching“ Modell geschätzt, in dem Daten von ,,U.S. National Cooperative Research Act“ benutzt werden.
Keywords: 330